Multi-modality Treatment and Survival in Sinonasal Minor Salivary Gland Tumors - Torabi, Sina J.; Spock, Todd; Cardoso, Bruno; Chao, Janet; Manes, R Peter; Judson, Benjamin L. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives The aim of this study was to analyze the effect of the multimodality treatment on survival in sinonasal minor salivary gland tumors.Methods Adult clinical American Joint Committee on Cancer (AJCC) tumor (T) 1-4a staged cases of sinonasal minor salivary gland tumors were isolated from the National Cancer Database (2004–2014). Multivariate regressions were performed to analyze the effect of multimodality treatment. A subset analysis was also performed in patients with positive margins following surgical management.Results We identified 556 cases, of which 293 (52.7%) patients were treated with surgery and radiotherapy (RT), 160 (28.8%) were treated with surgery alone, and 52 (9.4%) were treated with surgery and chemoradiotherapy (CRT). No patients were treated with chemotherapy alone. With surgery and CRT as a reference, the only treatment modality associated with decreased survival was RT alone (hazard ratio [HR]: 3.213 [95% confidence interval (CI): 1.578–6.543]; p = 0.001). Within a subset analysis of patients with positive margins, surgery was associated with decreased survival (HR: 2.021 [95% CI: 1.401–3.925]; p = 0.038), but not triple modality therapy (HR: 1.700 [95% CI: 0.798–3.662]) when compared with surgery with RT.Conclusion The most common treatment was surgery and RT, consistent with National Comprehensive Cancer Network (NCCN) guidelines which recommends chemotherapy (CT) only in the most concerning cases. However, we found no difference in survival among most treatment modalities when compared with triple modality therapy, with the exception of RT alone. Although margins were prognostic within these cancers, we found no evidence that adjuvant CRT provides any survival benefit over surgery and RT, though surgery alone was associated with decreased survival.
Keywords: sinonasal minor salivary gland tumors; NCDB; multimodality treatment; sinonasal tumors; outcomes